The Global Repercussions of the 1947 Symposium on Fish Populations in Toronto: Scientific Networks and the Over-fishing Question - Hubbard, Jennifer (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2018)
A relatively small, contentious, and long-forgotten meeting, the 1947 Symposium on Fish Populations, had enormous and decades-long repercussions for global fisheries policies. Convened in Toronto by Archibald Gowanlock Huntsman, former director of the Atlantic Biological Station, it drew together leading North American fisheries biologists and professional fishermen. By exposing the lack of agreement on, or understanding of, the nature of overfishing, this meeting made it difficult for later scientists to challenge pro-industry fisheries policies. The published proceedings, in-demand by a tight network of fisheries scientists across North America and the North Atlantic, guaranteed this meeting’s disproportionate and unfortunate impact.